THE JAPANESE ’MIRACLE’: TWO VIEWS - Burkes, Ardath W. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1982)
Nobuo K. Shimahara. ADAPTATION AND EDUCATION IN JAPAN. New York, N.Y.: Praeger Publishers, 1979. 19.95. William K. Cummings. EDUCATION AND EQUALITY IN JAPAN. Princeton, N.J.: Princeton University Press, 1980. 305 pp., 9.75 paper, 20.00 cloth.